Lipid composition of raw and grilled beef cattle slaughtered at four body weights (Research, Society and Development, 2020)
The fatty acid composition of beef can be altered by factors related to the animal, management, processing and preparation. The effect of body weight and cooking of meat on the composition of long chain fatty acids was evaluated. Forty 10-month old crossbred young bulls (½ Brown Swiss x ½ Nellore) of initial body weight 219 kg finished in feedlot with high grain diet and slaughtered with 450, 469, 491 and 513 kg of body weight. The Longissimus dorsi muscle was collected after slaughter and carcass chilling. The individual composition of the fatty acids of the meat was not altered (P < 0.05) by different body weights and by cooking (until reaching 72º C). Likewise, the sum of the percentages of saturated, monounsaturated, polyunsaturated, omega 3 and 6 fatty acids; as well as the ratios between monounsaturated/polyunsaturated fatty acids and omega 3 and 6 were not altered. Therefore, the different body weights and heating used in this study were insufficient to cause significant alterations in the fat molecules and the meat can be consumed without damaging the health of the consumer.